2019
DOI: 10.1371/journal.pone.0217804
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal microbiome profiling reveals impermanence of probiotic bacteria in domestic pigeons

Abstract: Probiotics are bacterial species or assemblages that are applied to animals and plants with the intention of altering the microbiome in a beneficial way. Probiotics have been linked to positive health effects such as faster disease recovery times in humans and increased weight gain in poultry. Pigeon fanciers often feed their show pigeons probiotics with the intention of increasing flight performance. The objective of our study was to determine the effect of two different probiotics, alone and in combination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 67 publications
0
15
1
Order By: Relevance
“…Catellicoccus were first described in 2006 following isolation from decomposing sea mammals (Lawson, Collins, Falsen, & Foster, ) and have subsequently been discovered to be a significant member of the gull faecal microbiome (Koskey, Fisher, Traudt, Newton, & McLellan, ; Lu, Santo Domingo, Lamendella, Edge, & Hill, ). Enterococcus , Staphylococcus , Lactobacillus , Enterobacter , Clostridium and Lactococcus were detected in at least one quarter of the samples and are all common gut microbes in birds (e.g., Grond, Perreau, et al, ; Liu et al, ; van Dongen et al, ; Waite & Taylor, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catellicoccus were first described in 2006 following isolation from decomposing sea mammals (Lawson, Collins, Falsen, & Foster, ) and have subsequently been discovered to be a significant member of the gull faecal microbiome (Koskey, Fisher, Traudt, Newton, & McLellan, ; Lu, Santo Domingo, Lamendella, Edge, & Hill, ). Enterococcus , Staphylococcus , Lactobacillus , Enterobacter , Clostridium and Lactococcus were detected in at least one quarter of the samples and are all common gut microbes in birds (e.g., Grond, Perreau, et al, ; Liu et al, ; van Dongen et al, ; Waite & Taylor, ).…”
Section: Discussionmentioning
confidence: 99%
“…and Lactococcus were detected in at least one quarter of the samples and are all common gut microbes in birds (e.g., Grond, Perreau, et al, 2019;Liu et al, 2019;van Dongen et al, 2013;Waite & Taylor, 2014).…”
Section: Enterococcus Staphylococcus Lactobacillus Enterobacter Cmentioning
confidence: 99%
“…Recent probiotics studies with pigeons revealed that pigeon milk microbiota, transmitted from parent pigeons to squabs, contain a considerable proportion of Lactobacillus and Bifidobacterium, but not Corynebacterium [ 118 ]. However, the dramatic effects of probiotics on microbiome profiling were demonstrated in Birmingham Roller pigeons [ 119 ]. Birmingham Roller pigeons have been domesticated for pigeon fancying due to the ability to perform backwards somersaults during flight.…”
Section: Soil and Gut Bacterium Scenario: L-glutamate Secretion Fomentioning
confidence: 99%
“…Interestingly, the pigeon gut microbiome is highly dependent on diet. When pigeons are fed only a diet of grain, actinobacteria is the most dominant phyla (more than 40% on average), and Corynebacterium is significantly abundant; however, when a probiotic diet was given, immediately a decrease in two genera ( Corynebacterium and Peptostreptococcus ) occurred, and the gut microbiome shifted towards a Firmicutes-dominated population, mainly by Lactobacillus, ranging from 71.8% to 99.9% in 14 days [ 119 ]. It was concluded that Corynebacterium and Peptostreptococcus are pathogens in the pigeon gut; therefore, reducing pathogen loads by probiotics helps the pigeon health.…”
Section: Soil and Gut Bacterium Scenario: L-glutamate Secretion Fomentioning
confidence: 99%
“…It has also been suggested, but not independently confirmed, that probiotic–microbiota interactions could impair microbiota reconstitution following its depletion by an antibiotic (Suez, Zmora et al, ). All would agree that a probiotic will disappear from the gastrointestinal tract soon after its administration has ceased (Grond et al, ).…”
Section: Probioticsmentioning
confidence: 99%